MEMBANGUN PARADIGMA DUNIA MODERN DAN ISLAM TERHADAP ILMU PENGETAHUAN - Nani Mulyani; Aep Saepul Anwar (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
The development of science and technology at this time is one of the achievements of progress in this modern age can be said to be achieved but sometimes also has a harmful impact on the continuity of human life, depending on how humans take advantage of this knowledge so that science and technology can provide values ​​of value (value ), but on the contrary the improper use of technology will result in destruction so that it cannot provide benefits (disvalue). To dismiss all of this so that it does not affect the inappropriate use of religion (Islam) is deemed necessary as a guide in the use of knowledge and knowledge in the right direction. Through the revelation of the Prophet Muhammad SAW with a set of Al-Qur'an and Hadith invites seeking and obtaining knowledge with full wisdom, and places people who are knowledgeable at a high level. The meeting of Islam with the modern world views science as giving birth to various understandings and thoughts, because basically knowledge develops because humans have a curiosity in achieving the highest reality.